UPAYA MENINGKATKAN SIFAT GOTONG ROYONG ANAK USIA DINI DALAM BERMAIN PERAN DI TK KENTEN PERMAI - Rizky Zahara; Taty Fauzi; Mardiana Sari (Jurnal Lentera Pedagogi, 2023)
This study aims to determine the mutual cooperation behavior of Early Childhood in playing activities at school. The method used is an Action Research design. The sample used was 15 children in group B at Kenten Permai Kindergarten, consisting of 7 boys and 8 girls. The data used were collected through observation, interviews, and documentation. The collected data were analyzed using quantitative and qualitative percentage formulas. As for the results of the study, there was an increase in the achievement of mutual cooperation in early childhood from pre-cycle to cycle I and to cycle II, in the pre-cycle the score was 20.13 in the undeveloped category, then in the first cycle there was an increase in score of 29.27 the category began to develop an increase of 9.14 while in the second cycle the score was 41.2, the category developed very well. This condition indicates that the second cycle has increased by 11.93. So it was concluded that the end of the second cycle was successful because the success criteria had been achieved in accordance with the predetermined targets